The role of supplementation in traumatic brain injury among athletes and non-athletes population - Pilawska, Sandra Agnieszka; Bado, Michał; Goncerz, Michał; Nowoświat, Patrycja; Bilecki, Krzysztof; Bednarczyk, Paulina; Malaka, Ewa Katarzyna; Duda, Weronika; Muzyk, Magdalena; Maślankiewicz, Maria (Quality in Sport, 2024)
Introduction: Traumatic brain injury (TBI) is one of the most common causes of death and long-term disability. The consequences following TBI can be persistent and cause life-long implications for survivors. Treatment of TBI may be complex and involve large monetary costs. The frequent injury mechanisms are traffic-related, falls, violence or sport-related accidents. Higher risk of brain injury and its complications indicate that people affected by brain trauma may benefit from the prophylactic and post-traumatic use of certain supplements both in the context of physical performance and in the event of potential injury. Aim of the Study: This narrative review examines the current literature of the role of supplementation before and after TBI and its effects on the patient's outcome. Materials and Methods: A comprehensive search was performed using PubMed and Google Scholar focusing on the literature published up to April 2024. The review included randomized controlled trials, meta-analyses, systematic reviews that focused on the use of creatine monohydrate, omega-3 fatty acids, magnesium and zinc in TBI and among the general population. Data of pathophysiology and epidemiology of TBI and safety profile of supplements were involved. Results: The evidence indicates that the role of supplementation with creatine, omega-3 PUFAs and zinc is important in mitigating secondary damage after TBI, as well as in protecting against damage if administered before injury. Conclusion: Because of the complex and multifactorial nature of the TBI more studies are required to constitute an effective nutrition-based strategy for reducing the cognitive and behavioral deficits associated with this injury. The evidence supporting multiple dietary components to improve a patient's outcome seems strong and the cost of its implementation is low. A group of particular interest that may benefit additionally are athletes who use dietary supplementation in their daily routine.